إتجاهات اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية نحو إستخدام التعليم المصغر في العملية التعليمية - بن عبد السلام عبد الرزاق (My University, 2023)
.....................................ABSTRACT.............................................................. The title of the study: the attitudes of the teachers of the Institute of Science and Technology of Physical and Sports Activities towards the use of micro-learning in the educational process. Objectives of the study : • Determining the degree to which the teachers of the Institute of Science and Technology of Physical and Sports Activities use the dismantling of the educational process. • Determining the degree of using the teachers of the Institute of Science and Technology of Physical and Sports Activities to minimize the educational situation. • Identifying the degree of using observation and self-evaluation by the teachers of the Institute of Science and Technology of Physical and Sports Activities. • Indicating the degree to which the teachers of the Institute of Science and Techniques of Physical and Sports Activities use feedback as "return feedback". Study problem: What is the degree of using the teachers of the Institute of Science and Technology of Physical and Sports Activities for micro-education in the educational process? Study hypotheses: The general hypothesis: The teachers of the Institute of Science and Technology of Physical and Sports Activities use micro-education in the educational process to a moderate degree. Partial hypotheses: • The teachers of the Institute of Science and Technology of Physical and Sports Activities use dismantling the educational process to a moderate degree. • The teachers of the Institute of Science and Technology of Physical and Sports Activities use minimizing the educational situation to a weak degree. • The professors of the Institute of Science and Technology of Physical and Sports Activities use observation and self-evaluation to a large extent. • The teachers of the Institute of Science and Technology of Physical and Sports Activities use the feedback "feed back" to a medium degree. Study sample: The research sample was chosen intentionally. They are the professors affiliated with the Institute of Science and Technology of Physical and Sports Activities at Muhammad Al-Sharif University, Souk Ahras, and their number consists of 30 professors of both sexes. The method used: the descriptive method The tool used in the study: A questionnaire was used for teachers of the Institute of Science and Technology of Physical and Sports Activities. The most important findings: • The teachers of the Institute of Science and Technology of Physical and Sports Activities use dismantling the educational process to a moderate degree. • The teachers of the Institute of Science and Technology of Physical and Sports Activities use minimizing the educational situation to a weak degree. • The professors of the Institute of Science and Technology of Physical and Sports Activities use observation and self-evaluation to a large extent. • The teachers of the Institute of Science and Techniques of Physical and Sports Activities use the feedback "feed back" to a medium degree. Suggestions:  The need to use micro-teaching at educational levels to provide teachers with teaching skills.  Increasing awareness of the concepts of micro-teaching and teaching competence and their role in the teaching process.  The need to use the teaching skills scale for the purpose of determining the extent of acquiring and developing teaching skills.  The possibility of applying micro-teaching in teaching methods lessons.  Conducting more research and studies that use the method of micro-teaching on other sports activities.  Using the mini-learning method in various educational purposes, such as training to master certain skills, and not only applying it on the cognitive side.  Employing micro-learning through the e-training environment as a modern trend in training that centers around the trainer and is based on providing training commensurate with his preferred training style.  The need to benefit from technological developments, teaching and learning theories, and the results of studies and research related to micro-learning to increase its effectiveness in various learning outcomes.  Introducing this strategy within the curricula and teaching methods curriculum in the faculties of education and basic education. .......................................................................ملخص الدراسة........................................................... عنوان الدراسة: اتجاهات اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية نحو استخدام التعليم المصغر في العملية التعليمية. أهداف الدراسة: • تحديد درجة استخدام اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية تفكيك العملية التعليمية. • تعيين درجة استخدام اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية تصغير الموقف التعليمي. • التعرف على درجة استخدام اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية المشاهدة والتقويم الذاتيين. • تبيين درجة استخدام اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية التغذية الراجعة "رجع المردود. مشكلة الدراسة: ما درجة استخدام اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية للتعليم المصغر في العملية التعليمية؟ فرضيات الدراسة: الفرضية العامة: يستخدم اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية التعليم المصغر في العملية التعليمية بدرجة متوسطة. الفرضيات الجزئية:  يستخدم اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية تفكيك العملية التعليمية بدرجة متوسطة.  يستخدم اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية تصغير الموقف التعليمي بدرجة ضعيفة.  يستخدم اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية المشاهدة والتقويم الذاتيين بدرجة كبيرة.  يستخدم اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية التغذية الراجعة "رجع المردود" بدرجة متوسطة. عينة الدراسة: عينة البحث تم اختيارها بطريقة قصدية، هم الاساتذة التابعين لمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة محمد الشريف مساعدية سوق اهراس و يتكون عددهم من 30 استاذ من كلا الجنسين. المنهج المتبع: المنهج الوصفي. الأداة المستخدمة في الدراسة: حيث تم استخدام استمارة استبيان موجهة لأساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية. أهم النتائج المتوصل إليها:  أن اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية يستخدمون تفكيك العملية التعليمية بدرجة متوسطة.  أن اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية يستخدمون تصغير الموقف التعليمي بدرجة ضعيفة.  أن اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية يستخدمون المشاهدة والتقويم الذاتيين بدرجة كبيرة.  أن اساتذة معهد علوم وتقنيات النشاطات البدنية والرياضية يستخدمون التغذية الراجعة "رجع المردود" بدرجة متوسطة. الإقتراحات: وجوب استخدام التدريس المصغر في المستويات التعليمية لإكساب وتزويد المعلمين بمهارات التدريس. زيادة الوعي بمفهومي التدريس المصغر والكفاية التدريسية ودورهما في عملية التدريس. ضرورة استخدام مقياس مهارات التدريس لغرض الوقوف على مدى اكتساب وتطوير مهارات التدريس. امكانية تطبيق التدريس المصغر في دروس طرائق التدريس. إجراء مزيد من البحوث و الدراسات التي تستخدم أسلوب التدريس المصغر على الأنشطة الرياضية الأخرى. استخدام أسلوب التعلم المصغر في الأغراض التعليمية المختلفة كالتدريب على إتقان مهارات معينة وعدم الإكتفاء بتطبيقه على الجانب المعرفي فقط. توظيف التعلم المصغر عبر بيئة التدريب الإلكتروني باعتبارها اتجاها حديثا في التدريب يتمركز حول المدرب ويقوم على تقديم تدريب يتناسب ونمط التدريب المفضل لديه. ضرورة الإستفادة من التطورات التكنولوجية، ونظريات التعليم والتعلم، ونتائج الدراسات والبحوث ذات الصلة بالتعلم المصغر لزيادة فاعليته في نواتج التعلم المتنوعة. إدخال هذه الاستراتيجية ضمن منهاج مادة المناهج وطرائق التدريس في كليات التربية و التربية الأساسية. ...................................................................résumé......................................................... Le titre de l'étude : les attitudes des enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives face à l'utilisation du micro-apprentissage dans le processus éducatif. les objectifs des études : • Déterminer dans quelle mesure les enseignants de l'Institut des sciences et technologies des activités physiques et sportives utilisent le démantèlement du processus éducatif. • Déterminer le degré d'utilisation des enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives pour minimiser la situation éducative. • Identifier le degré d'utilisation de l'observation et de l'auto-évaluation par les enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives. • Indiquer dans quelle mesure les enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent le feedback comme « retour d'information ». Problème d'étude : Quel est le degré d'utilisation des enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives pour la micro-éducation dans le processus éducatif ? Hypothèses d'étude : L'hypothèse générale : Les enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent modérément la micro-éducation dans le processus éducatif. Hypothèses partielles :  Les enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives ont un recours modéré au démantèlement du processus éducatif.  Les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent la minimisation de la situation éducative à un faible degré.  Les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent largement l'observation et l'auto-évaluation.  Les enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent le feedback « feed back » à un degré moyen. Échantillon de l'étude : L'échantillon de recherche a été choisi intentionnellement. Il s'agit des professeurs affiliés à l'Institut des sciences et technologies des activités physiques et sportives de l'Université Muhammad Al-Sharif, Souk Ahras, et leur nombre est de 30 professeurs des deux sexes. La méthode utilisée : la méthode descriptive. L'outil utilisé dans l'étude : Un questionnaire a été utilisé pour les enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives. Les découvertes les plus importantes :  Les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives ont un recours modéré au démantèlement du processus éducatif.  Les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent la minimisation de la situation pédagogique à un faible degré.  Les professeurs de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent largement l'observation et l'auto-évaluation.  Les enseignants de l'Institut des Sciences et Techniques des Activités Physiques et Sportives utilisent le feedback « feed back » à un degré moyen. Suggestions: La nécessité d'utiliser le micro-enseignement aux niveaux éducatifs pour doter les enseignants de compétences pédagogiques. Accroître la sensibilisation aux concepts de micro-enseignement et de compétence pédagogique et à leur rôle dans le processus d'enseignement. La nécessité d'utiliser l'échelle des compétences pédagogiques pour déterminer le degré d'acquisition et de développement des compétences pédagogiques. La possibilité d'appliquer le micro-enseignement dans les cours de pédagogie. Mener plus de recherches et d'études qui utilisent la méthode du micro-enseignement sur d'autres activités sportives. Utiliser la méthode de mini-apprentissage à diverses fins éducatives, telles que la formation pour maîtriser certaines compétences, et pas seulement l'appliquer sur le plan cognitif. L'utilisation du micro-apprentissage via l'environnement de formation en ligne comme une tendance moderne de la formation centrée sur le formateur et basée sur la fourniture d'une formation correspondant à son style de formation préféré. La nécessité de tirer parti des développements technologiques, des théories d'enseignement et d'apprentissage et des résultats d'études et de recherches liées au micro-apprentissage pour accroître son efficacité dans divers résultats d'apprentissage. Introduire cette stratégie dans les programmes d'études et de pédagogie des facultés d'éducation et d'éducation de base.
دراسة ميدانية على مستوى معهد علوم وتقنيات النشاطات البدنية والرياضية – سوق أهراس -